AMPK controls the axonal regenerative ability of dorsal root ganglia sensory neurons after spinal cord injury - Kong, Guiping; Zhou, Luming; Serger, Elisabeth; Palmisano, Ilaria; Virgiliis, Francesco de; Hutson, Thomas H.; Mclachlan, Eilidh; Freiwald, Anja; La Montanara, Paolo; Shkura, Kirill; Puttagunta, Radhika; Di Giovanni, Simone (Nature metabolism, 2020)
Regeneration after injury occurs in axons that lie in the peripheral nervous system but fails in the central nervous system, thereby limiting functional recovery. Differences in axonal signalling in response to injury that might underpin this differential regenerative ability are poorly characterized. Combining axoplasmic proteomics from peripheral sciatic or central projecting dorsal root ganglion (DRG) axons with cell body RNA-seq, we uncover injury-dependent signalling pathways that are uniquely represented in peripheral versus central projecting sciatic DRG axons. We identify AMPK as a crucial regulator of axonal regenerative signalling that is specifically downregulated in injured peripheral, but not central, axons. We find that AMPK in DRG interacts with the 26S proteasome and its CaMKIIα-dependent regulatory subunit PSMC5 to promote AMPKα proteasomal degradation following sciatic axotomy. Conditional deletion of AMPKα1 promotes multiple regenerative signalling pathways after central axonal injury and stimulates robust axonal growth across the spinal cord injury site, suggesting inhibition of AMPK as a therapeutic strategy to enhance regeneration following spinal cord injury.